Proteomic-components provide insights into the defensive secretion in termite workers of the soldierless genus Ruptitermes - Costa-Leonardo, Ana Maria [UNESP]; da Silva, Iago Bueno [UNESP]; Poiani, Silvana Beani [UNESP]; dos Santos-Pinto, José Roberto Aparecido [UNESP]; Esteves, Franciele Grego [UNESP]; da Silva, Luiza Helena Bueno [UNESP]; Palma, Mario Sergio [UNESP] (Elsevier, 2020)
Termite soldiers constitute the defensive frontline of the colonies, despite workers also perform such tasks, especially within the Neotropical Apicotermitinae, in which all species are soldierless. Workers of the genus Ruptitermes display an extreme form of defense, characterized by body rupture and release of a sticky secretion. Previous observations suggested that such behavior may be advantageous against enemies, but the chemical composition of this secretion has been neglected. Here we firstly provide the proteomic profile of the defensive secretion of Ruptitermes reconditus and Ruptitermes pitan workers. Additionally, the mechanisms of action of this behavior was evaluated through different bioassays. A total of 446 proteins were identified in R. reconditus and 391 proteins in R. pitan, which were classified into: toxins, defensins and proteolytic enzymes; sticky components/ alarm communication; proteins related to detoxification processes; proteins involved in folding/conformation and post-translational modifications; housekeeping proteins; and uncharacterized/hypothetical proteins. According to the bioassays, the self-sacrifice is triggered by a physical stimulus, and the defensive secretion may cause immobility and death of the opponents. Assuming that termites are abundant in the tropics and therefore exposed to predators, suicidal behaviors seem to be advantageous, since the loss of an individual benefit the whole colony. Significance: Although recent studies have reported the biochemical composition of different weapons in soldiered species of termites, such efforts had not been applied to sordierless taxa up until now. Thus, this is the first report of the defensive mechanisms in soldierless termite species based on proteomic analysis. The diversity of compounds, which included toxin-like and mucin-like proteins, reflect the mechanisms of action of the defensive secretion released by termite workers, which may cause immobility and death of the opponents. Our findings may contribute to the knowledge regarding the development of defensive strategies in termites, especially in groups which lost the soldier caste during the evolution.
Keywords: Apicotermitinae; Isoptera; LCMS-based proteomics; Mucin-like proteins; Sticky defensive secretion; Toxin-like proteins